2010
DOI: 10.1120/jacmp.v11i4.3268
|View full text |Cite
|
Sign up to set email alerts
|

Portal dosimetry for pretreatment verification of IMRT plan: a comparison with 2D ion chamber array

Abstract: Portal dosimetry (PD) was performed for 181 fields from 14 IMRT plans of various clinical sites at gantry zero and source‐to‐detector distance (SDD) of 100 cm. PD was realized using aSi1000 electronic portal imaging device (EPID) and portal dose prediction (PDP) algorithm implemented in Eclipse treatment planning system (TPS). Agreement of PDP predicted and EPID measured photon fluence/dose distribution were evaluated using gamma (γ) index set at 3% at 3 mm distance to point agreement (DTA). Three gamma scalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 27 publications
0
27
0
2
Order By: Relevance
“…Although the primary purpose of EPID is to verify patient positioning, but with the introduction of on board imagers for image guidance the EPID has been more utilised for machine QA and pre-treatment patient specific QA [11][12][13][14]. Dosimetry using EPIDs or portal dosimetry has received considerable attention recently due to its relatively high-resolution of 0.392mm amorphous silicon (a-Si) flat-panel detector [15][16][17][18]. Several authors have extensively studied the dosimetric properties of a-Si 500 and a-Si 1000 EPID and its application in IMRT [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Although the primary purpose of EPID is to verify patient positioning, but with the introduction of on board imagers for image guidance the EPID has been more utilised for machine QA and pre-treatment patient specific QA [11][12][13][14]. Dosimetry using EPIDs or portal dosimetry has received considerable attention recently due to its relatively high-resolution of 0.392mm amorphous silicon (a-Si) flat-panel detector [15][16][17][18]. Several authors have extensively studied the dosimetric properties of a-Si 500 and a-Si 1000 EPID and its application in IMRT [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Bakhiari et al 1) used a 38% isointensity line of cine EPID images to verify multileaf collimator (MLC) leaf positions during VMAT delivery. Sharma et al 2) tested the EPID portal dosimetry for IMRT QA using 181 intensity modulated fields that was compared to a two-dimensional (2D) ion chamber array (MatriXX, IBA, Louvain-la-Neuve, Belgium), and concluded that both fluence verification methods produced comparable QA results. Clemente et al 3) reported that the portal dosimetry was a useful QA tool for dynamic and static IMRT delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have investigated the use of electronic portal imaging devices for quality assurance purposes such as MLC position verification (16)(17)(18) and IMRT patient specific dose verification (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Renner et al (24) reported on four different methods that have been introduced for the purpose of using the EPID for treatment verification: 1) Compute the dose from each beam to the EPID and compare to the actual EPID image of each beam (4-15); 2) Use the EPID to verify the leaf positions for intensity modulated fields (16)(17)(18); 3) Reconstruct the dose to the patient using the exit image acquired during treatment (20)(21)(22)(23); and 4) Convert the EPID images to an incident fluence distribution and use it for dose calculation employing the patient CT anatomy (24,25).…”
Section: Introductionmentioning
confidence: 99%